Construction contracts : questions and answers - Chappell, David (David M.) (Abingdon, Oxon ; New York : Routledge, 2021)
"This fully revised and updated edition of Construction contracts : Questions and answers includes 300 questions and incorporates 42 new judicial decisions, the JCT 2016 updates and the RIBA Building Contracts and Professional Services Contracts 2018 updates"--
OCLC-licensed vendor bibliographic record.
Keywords: Construction contracts -- Great Britain; Construction contracts -- Great Britain -- Miscellanea; LAW / Construction; TECHNOLOGY / Construction / Contracting